"Frequent Deaths": The Colonial Development of Concentration Camps Reconsidered, 1868–1974. Issue 3 (3rd July 2018) - Stucki, Andreas
ABSTRACT: This article sheds new light on the development of concentration camps in colonial warfare in the longue durée from 1868 to 1974. Introducing different examples of forced removal and deportation in the Spanish and Portuguese empires, the analysis emphasizes their interrelation, highlighting possible transfers of knowledge that have been neglected in comparative discussions. Specifically, the article reassesses the Cuban experience of concentrating civilians in times of war (1868–98); it critically evaluates Spain's forgotten concentration camps on the Canary Islands, which emerged during the Ifni-Sahara war of 1957–58; and it focuses on both the theory of revolutionary warfare and the practice of so-called strategic resettlement in the long and protracted Portuguese colonial wars in Africa (1961–74). In particular, the camps on the Canary Islands suggest the need for an analytical distinction between the function of forced removals in counter-guerrilla warfare and administrative internment; they are related but essentially different policies. Based on hitherto ignored archival material, this empirically supported analysis challenges common assumptions about the "origins" of camps, and questions traditional temporal boundaries in the development of (anti-)guerrilla warfare.